Exploring the Effect of Outpatient Cardiac Rehabilitation on Prevention of Short‐term Re‐admission: A Hospital‐based Study in Fukushima, Japan. (18th June 2016) - Endo, Noriko; Goto, Aya; Suzuki, Tomoko; Yasumura, Seiji
Abstract : Objective: This hospital‐based study examined whether outpatient cardiac rehabilitation (CR) prevents cardiac‐related re‐admission within 6 months. Method: Clinical records of Japanese cardiac disease patients who were hospitalized and recommended for cardiac rehabilitation at a general hospital were analyzed by comparing data from 78 outpatient CR (OCR) participants with data from 179 randomly selected non‐participants. Results: OCR significantly prevented cardiac‐related re‐admission (odds ratio: 0.24; 95% confidence interval: 0.06–0.91) after controlling for sex and OCR participation‐associated factors. Conclusion: OCR participation may improve short‐term prognosis. The positive effects of OCR should be promoted to increase participation.